Moroccan Migration in Belgium : More than 50 Years of Settlement - Vanheule, Dirk; Praag, Lore Van; Levrau, François; Clycq, Noel; Timmerman, Christiane (CeMIS Migration and Intercultural Studies, 2018)
Thought-provoking insights on the nexus of migration and integration beyond the national context0Across the world, and due to ongoing globalisation, migration is increasingly becoming a part of daily life. But more than ever, migration can no longer be viewed as a simple linear trajectory from A to B. The emergence of transnational communities and intense interactions between regions of origin and of destination have led to new forms of social?cultural praxis and (sub)cultures which exert an important influence on the integration of immigrants. The case of Flanders, the northern part of Belgium and at the centre of EU policymaking, is presented as a case study in this book.